Aluminum and iron biomass pretreatment impacts on biochar anion exchange capacity. (July 2017) - Lawrinenko, Michael; Jing, Dapeng; Banik, Chumki; Laird, David A.
Abstract: Some biochars have significant anion exchange capacity (AEC) under acidic pH conditions but typically have little or no AEC at neutral to alkaline pHs. We hypothesized that metal oxyhydroxide surface coatings on biochar will increase biochar anion exchange capacity (AEC) at higher pHs by virtue of the high point of zero net charge of metal oxyhydroxides. Here we report that pyrolysis temperature and the distribution of metal oxyhydroxides in biochars prepared by slow pyrolysis of biomass pre-treated with Al or Fe trichlorides strongly influenced biochar AEC. Biochars produced at 700 °C exhibit greater AEC than biochars similarly prepared at 500 °C. Spectroscopic ( FTIR, XPS, and SEM-EDS ) studies provided evidence for the formation of AlOC organometallic moieties on biochar surfaces that formed during pyrolysis. To a lesser extent, Fe also formed FeOC surface structures on biochar, but most Fe was present in discrete crystalline phases ranging from zerovalent iron to ferric oxides. These organometallic bonding structures are a means of supporting metal oxides on biochar carbon and are responsible for broader metal atom distributions, which can increase AEC through the development of metal oxyhydroxide surface coatings that exhibit high points of zero net charge. Graphical abstract: